Evaluation of optic nerve head parameters and visual evoked potential among breast cancer patients on tamoxifen - Lee, Tan Chai (2017)
Background: Tan1oxifen retinopathy and optic neuropathy is a known complication of tatnoxifen treatment. Scanning confocal laser ophthahnoscopy of optic nerve head detnonstrated sn1aller optic cup in visually asymptomatic patients on tatnoxifen. Electrophysiology study is a non-invasive method of evaluating retinal function and facilitate differentiation between retinal and optic nerve dysfunction. The present study aitns to evaluate early optic nerve head paran1eter and electrophysiology changes in patients receiving tan1oxifen. Method: This is a prospective study involving 76 eyes of 38 breast cancer patients treated with Tamoxifen in Hospital Universiti Sains Malaysia, Kelantan, Malaysia. These patients '"'ere exatnined by a single doctor and the investigations were done by a single technician. The visual acuity, optic nerve function, visual field, anterior and posterior segtnent ocular exatnination, optic nerve head paratneters n1easure1nent on 1-Ieidelbcrg Retinal Ton1ograph III (HRT TIT) and Pattern VEP were assessed. The exmnination was performed before and three tnonths after treatment initiation.Results: There was no ta1noxifen ocular toxicity found 3 months post treatment with tamoxifen. There was no change in visual acuity and optic nerve function post treatment initiation. There were no statistically significant changes found in optic nerve head paran1eters on IIRT III and P 100 peak latency and mnplitude on PVEP within study duration. Conclusion: Ocular toxicity is a recognized con1plication of tamoxifen trcattnent. Tan1oxifen optic neuropathy is a potentially irreversible, visually disabling complication. Tatnoxifen ocular toxicity was not found 3 1nonths after tatnoxifen treattnent initiation atnong breast cancer patients. No early changes in optic nerve head paratneters and P 100 peak latency and atnplitudc changes found after 3 tnonths of treatment. Longer duration of tnonitoring \Vith HRT III and Pattern VEP tnay be needed to adequately observe for early, subclinical changes in optic nerve head parameters and visual function mnong tmnoxifen users.